Homo Faber: a Philosophy of Technology and Ethical Implications - Paul Rohan, J.C. (Jnana-Deepa Vidyapeeth, Pune, 2019)
Homo faber is the name that is attributed to the human being in the process of technological development and it is also seen as one of the stages of human growth and a product of homo sapiens. Technology has become an omnipresent phenomenon today in all the dimensions of human existence on earth. It is considered the most essential ingredient of human life that the technological equipments are supposed to be sine qua non conditions even for an ordinary way of living. Many superstitions and needless sufferings of the past have been eliminated. The present condition of human life with all its comforts, facilities and safety are to be attributed to the development of technology. Human progress would not have been realized without technological advancements. The constant growth in technology promises a new age of opportunity in all the human affairs. The tremendous growth of technology and its domination over mankind is expressed today by the terms megatechnology or technocracy. However, there are many issues raised by the impact of technology on the human beings. The immense growth of technology has endowed the human agent with the capacity of destroying even the very conditions upon which life depends. The power of modern technology has changed the whole notion of human existence and there is a serious invitation for all, to reflect about the technological determinism and the potential threats to the human being and the environment posed by technicalization of life. The efforts to safeguard the integrity of the living world in the midst of the current technological crises must be taken by formulating the ethical imperatives for technological age. A formulation of a philosophy of technology is required to look for an ethics based on responsibility and to deal with the deterministic character of technology. This article poses an invitation to contribute to the construction of a new humanism based on integral human values and concern for the environment.
Keywords: Homo Faber; technê; Technocracy; Technicalization; Human Ascent; Baconian Programme; Technological Nihilism; Faustian Soul; Efficient Ordering; Biotechnology